The intelligent person's guide to good governance - Munshi, Surendra (Sage Publications India, 2009)
From publisher's description: This book takes the discourse on governance beyond its self-inflicted narrow perspective by providing an integrated treatment of various relevant issues, for example, the role of the state or the idea of civil society. In carrying out a lucid analysis of a fluid concept, this book offers a 'one-stop' resource for understanding the subject. The central argument of the book that any serious engagement with good governance must go beyond an exclusive reliance on the state or the market and explore different modes of partnerships, including public participation, is relevant and indeed timely in the present crisis